Sprememba p.R577X gena ACTN3 (rs1815739) je povezana s pojavnostjo poškodb slovenskih nogometašic - Sotlar, Inge (Laboratorijska medicina, 2021)
Alpha-actinin-3 is a protein expressed in fast-twitch (type II) muscle fibres. ACTN3 gene variant NM_001104.4:c.1729C>T (p.R577X, rs1815739) in a homozygous state reduces strength, muscle mass, and fast-twitch fibre diameter and was asso-ciated with a higher risk of sports injuries and longer exer-cise recovery. We aimed to evaluate the association of the p.R577X with injuries and player position in Slovenian fema-le football players. The study group included 43 participants, with a median age of 16 (13-28) years, who had been acti-vely training football for at least 4 years. ACTN3 p.R577X genotyping was performed with PCR and DdeI restricti-on analysis on saliva DNA. p.R577X in the homozygous or heterozygous state was present in 58.1 % of the players, while 41.9 % had normal genotype. 53.7 % had a four ye-ars history of at least one sports injury. In our study, no sta-tistically significant association was found between ACTN3 p.R577X genotypes and the presence of injuries (p = 0.309), nor between the presence of injuries and player position (p = 0.830) or age dependant category team (p = 0.427). However, we confirmed the association between the presence of inju-ries and the frequencies of each allele (p = 0.037), with the X allele being associated with a higher incidence of injuries.
Keywords: ACTN3; female football players; genotipizacija; nogometašice; sports injuries; športne poškodbe